Quality of antenatal care in 13 sub-Saharan African countries in the SDG era: evidence from Demographic and Health Surveys - Edward Kwabena Ameyaw; Linus Baatiema; Ambrose Naawa; Frederick Odame; Doris Koramah; Francis Arthur-Holmes; Shadrack Osei Frimpong; Celestin Hategeka (BMC, 2024)
Abstract Background Maternal and neonatal mortality remains high in sub-Saharan Africa (SSA) with women having 1 in 36 lifetime risk. The WHO launched the new comprehensive recommendations/guidelines on antenatal care (ANC) in 2016, which stresses the essence of quality antenatal care. Consequently, the objective of this cross-sectional study is to investigate the quality of ANC in 13 SSA countries. Methods This is a cross-sectional study that is premised on pre-existing secondary data, spanning 2015 to 2021. Data for the study was obtained from the Measure DHS Programme and included a total of 79,725 women aged 15-49 were included. The outcome variable was quality ANC and it was derived as a composite variable from four main ANC services: blood pressure taken, urine taken, receipt of iron supplementation and blood sample taken. Thirteen independent variables were included and broadly categorised into individual and community-level characteristics. Descriptive statistics were used to present the proportion of women who had quality ANC across the respective countries. A two-level multilevel regression analysis was conducted to ascertain the direction of association between quality ANC and the independent variables. Results The overall average of women who had quality ANC was 53.8% [CI = 51.2,57.5] spanning from 82.3% [CI = 80.6,85.3] in Cameroon to 11% [CI = 10.0, 11.4] in Burundi. Women with secondary/higher education had higher odds of obtaining quality ANC compared with those without formal education [aOR = 1.23, Credible Interval [Crl] = 1.10,1.37]. Poorest women were more likely to have quality ANC relative to the richest women [aOR = 1.21, Crl = 1.14,1.27]. Married women were more likely to receive quality ANC relative to those cohabiting [aOR = 2.04, Crl = 1.94,3.05]. Women who had four or more ANC visits had higher odds of quality ANC [aOR = 2.21, Crl = 2.04,2.38]. Variation existed in receipt of quality ANC at the community-level [σ2 = 0.29, Crl = 0.24,0.33]. The findings also indicated that a 36.2% variation in quality ANC is attributable to community-level factors. Conclusion To achieve significant improvement in the coverage of quality ANC, the focus of maternal health interventions ought to prioritise uneducated women, those cohabiting, and those who are unable to have at least four ANCs. Further, ample recognition should be accorded to the existing and potential facilitators and barriers to quality ANC across and within countries.